System rządów Rzeczypospolitej Polskiej jako uwarunkowanie polskiej polityki wschodniej - Habowski, Mirosław (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2013)
The author of the article proposes a thesis that the constitutional regulations represent only one out of many factors that affect the existing political system in Poland. Considerably more important was the level of the parliamentary fragmentation, relations between the government and the president as well as balance of power between their political bases. The author considers consensus between the fundamental authorities, the fact of having avoided situations where mutual conflicts might have been exploited by external subjects (e.g. Russia) and elaboration of a realistic Eastern policy programme by the elites, to be the most important factors affecting efficacy of the Polish Eastern policy. Given this context, the regime evolution towards the model similar to the German Chancellor’s system seems to be legitimate
Keywords: polityka wschodnia; Ukraina; Federacja Rosyjska; Unia Europejska; NATO; relacje polsko-ukraińskie; stosunki polsko-rosyjskie; Kościół katolicki; kościół prawosławny; dyplomacja publiczna; bezpieczeństwo